PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA TEMA EKOSISTEM KELAS 5 SDN MALANGNENGAH 01 - Sulysiyah, Siti; Syachruroji, A.; Nulhakim, Lukman; Andriana, Encep (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This research aims to determine the process of implementing the project-based learning model in grade 5 students at SDN Malangnengah 01 and to determine the increase in students' conceptual understanding of the ecosystem theme through the project-based learning model in grade 5 SDN Malangnengah 01. This research uses a qualitative approach with the type Classroom Action Research which was carried out on 10 grade 5 students at SDN Malangnengah 01 in the odd semester of 2023. Data collection used observation, interviews and tests. The results of the research explain that: 1) the process of implementing the project-based learning model for grade 5 students at SDN Malangnengah 01 goes through 6 stages, namely problem recognition, determining basic questions/collecting information, designing product plans, preparing production schedules, monitoring student activity and product development, testing the results and finally the evaluation and reflection stage. Students can complete the project in 2 cycles, however in this case there are several notes such as incomplete student attendance, some still look lethargic and lack enthusiasm; 2) The project-based learning model can improve the understanding of science concepts for grade 5 students at SDN Malangnengah. This is known from the comparison of students' understanding of science concepts in each cycle which has increased significantly. In the pre-cycle, there were 3 students in the complete category with a percentage of 30%. After conducting classroom action research using a project-based learning model, this increased to 6 students with a percentage of 60% in cycle I, then experienced an increase again in cycle II. to 10 students or in other words reaching a percentage of 100%.